Armenia : Better Understanding International Labor Mobility - Honorati, Maddalena (World Bank, Washington, DC, 2019)
Armenia has experienced massive outflows of its people over years. Emigrants’ share of the Armenian population stood at approximately thirty-two percent in 2017, according to migration data from the United Nations (UN). Half of Armenian emigrants reside in Russia. Other key destinations include Azerbaijan, the United States and Ukraine. Recent migration is primarily temporary labor migration, unlike the permanent emigration that occurred in the 1990s. Remittances resulting from migration constitute important support to the welfare of households and the domestic economy. Nevertheless, the effects of remittances and migration on labor markets are not fully understood. As migration is likely to continue, such questions are still timely and relevant. The Russian-Armenian University (RAU) survey data indicate that about as many people would like to migrate as are current first-time migrants. This policy brief aims to explore and address the two questions about migration and its effects on the labor market in Armenia. It uses data from the household migration surveys conducted by the RAU over the three-year period of 2015-2017. The brief describes the general landscape of temporary labor migration and presents relevant policy recommendations.